2021
DOI: 10.1021/acs.jpcb.1c00684
|View full text |Cite
|
Sign up to set email alerts
|

Protein–Polymer Interaction Characteristics Unique to Nanoscale Interfaces: A Perspective on Recent Insights

Abstract: Protein interactions at polymer interfaces represent a complex but ubiquitous phenomenon that demands an entirely different focus of investigation than what has been attempted before. With the advancement of nanoscience and nanotechnology, the nature of polymer materials interfacing proteins has evolved to exhibit greater chemical intricacy and smaller physical dimensions. Existing knowledge built from studying the interaction of macroscopic, chemically alike surfaces with an ensemble of protein molecules cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 94 publications
1
17
0
Order By: Relevance
“…While QCMD data can also be used to confirm the formation of complexes and the kinetics of complexation, SAXS data provides additional information about the conformation of the complexes. The results we have obtained will also be useful in addressing a broader question of the structural changes that occur in proteins at polymer interfaces 58,60 …”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…While QCMD data can also be used to confirm the formation of complexes and the kinetics of complexation, SAXS data provides additional information about the conformation of the complexes. The results we have obtained will also be useful in addressing a broader question of the structural changes that occur in proteins at polymer interfaces 58,60 …”
Section: Discussionmentioning
confidence: 88%
“…The results we have obtained will also be useful in addressing a broader question of the structural changes that occur in proteins at polymer interfaces. 58,60 Our preliminary work with covalently immobilized enzymes provided justification for conducting adsorption experiments directly on gold sensors (Figure S1). Experiments at different HRP concentrations was useful in selecting the appropriate concentration of HRP (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important goal of the chemical cross-linking technique is the 3D networkstructure PBH's production through the formation of resistant and solid covalent bonds within its network [34,61]. The covalent cross-linking of target residues and particular chains on proteins [62][63][64], chemical coupling [19,65], and click reactions [66][67][68] are some of the chemical cross-linking approaches that have been reported.…”
Section: Protein-based Hydrogelsmentioning
confidence: 99%
“…We have made research efforts in this regard. ,, For example, we have shown that globular proteins such as immunoglobulin G (IgG), serum albumin (SA), and horseradish peroxidase (HRP) exclusively adsorb onto the polystyrene (PS) nanodomain regions, leaving the neighboring poly­(methyl methacrylate) (PMMA) nanodomain areas completely free of proteins on the BCP surface of PS- block -PMMA (PS- b -PMMA). ,,, The highly selective adsorption of the globular proteins to PS over PMMA observed on the nanoscale BCP surface is distinct from their behaviors onto chemically homogeneous, bulk, or macroscopic scale polymer surfaces. , For example, when homopolymer surfaces of PS and PMMA were used instead, the proteins were found to adsorb not only on PS but also on PMMA …”
Section: Introductionmentioning
confidence: 99%